2009
DOI: 10.1016/j.pmrj.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Ankle‐Foot Orthosis on Temporal Spatial Parameters and Asymmetry of Gait in Hemiparetic Patients

Abstract: Objective: To investigate the effect of an ankle-foot orthosis (AFO) on certain walking parameters in patients with hemiplegia. Design: Retrospective study. Setting: Gait and Motion Analysis Laboratory at MossRehab. Participants: A total of 1150 records of patients with stroke who were referred to the Gait and Motion Analysis Laboratory between 2000 and 2008 for an evaluation of their walking. Of this group, 217 patients wore braces at the time of the gait evaluation and were selected for a more in-depth revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 13 publications
(14 reference statements)
1
36
3
Order By: Relevance
“…69 The lack of difference in double support time suggests that neither device significant affects dynamic balance. The lack of difference in cadence between device conditions, while not consistent with prior gait analyses by Esquenazi et al 5 and Ring et al 7 who reported improvement in cadence with an AFO and tPNS device, respectively, may similarly be due to the relatively short distances ambulated.…”
Section: Discussioncontrasting
confidence: 57%
“…69 The lack of difference in double support time suggests that neither device significant affects dynamic balance. The lack of difference in cadence between device conditions, while not consistent with prior gait analyses by Esquenazi et al 5 and Ring et al 7 who reported improvement in cadence with an AFO and tPNS device, respectively, may similarly be due to the relatively short distances ambulated.…”
Section: Discussioncontrasting
confidence: 57%
“…In a retrospective study by Esquinazi et al31 ) in a three-dimensional gait lab, Moss Rehabilitation Engineering Center, in the spatiotemporal aspects of gait of 42 patients were evaluated and a significant improvement in both the speed and cadence of gait of the patients using AFO orthoses: (0.31 m/s) × speed with AFO (0.41 m/s), p<0.001; and cadence without AFO (63.3 steps/min) × cadence with AFO (68.8 steps/min), p<0.001.…”
Section: Discussionmentioning
confidence: 99%
“…greater hip involvement) [5]. An AFO can help compensate for plantarflexor weakness and improve walking economy by both stabilizing the ankle joint [6] and utilizing elastic storage and return from AFO deformation during stance [7,8].…”
Section: Introductionmentioning
confidence: 99%